2005
DOI: 10.1002/cm.20094
|View full text |Cite
|
Sign up to set email alerts
|

Balanced levels of Espin are critical for stereociliary growth and length maintenance

Abstract: Hearing and balance depend on microvilli-like actin-based projections of sensory hair cells called stereocilia. Their sensitivity to mechanical displacements on the nanometer scale requires a highly organized hair bundle in which the physical dimension of each stereocilium is tightly controlled. The length and diameter of each stereocilium are established during hair bundle maturation and maintained by life-long continuing dynamic regulation. Here, we studied the role of the actin-bundling protein Espin in ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
75
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 66 publications
(81 citation statements)
references
References 28 publications
6
75
0
Order By: Relevance
“…Transfection with espin constructs elicits pronounced microvillar PAB elongation both in epithelial cell lines in culture and in epithelial cells in tissue explants [13,34]. A significant lengthening effect can even be observed for the stereociliary PABs of transfected hair cells [34], even though they already express a large amount of espin endogenously. Conversely, as mentioned above, a major consequence of the espin deficiency noted in jerker mice is a marked shortening of stereocilia.…”
Section: Increasing the Steady-state Length Of Pabsmentioning
confidence: 99%
See 2 more Smart Citations
“…Transfection with espin constructs elicits pronounced microvillar PAB elongation both in epithelial cell lines in culture and in epithelial cells in tissue explants [13,34]. A significant lengthening effect can even be observed for the stereociliary PABs of transfected hair cells [34], even though they already express a large amount of espin endogenously. Conversely, as mentioned above, a major consequence of the espin deficiency noted in jerker mice is a marked shortening of stereocilia.…”
Section: Increasing the Steady-state Length Of Pabsmentioning
confidence: 99%
“…Occasional defects, such as protrusion and folding of the cuticular plate, were also noted in the cochlear hair cells of newborn jerker mice. The stereocilia of newborn jerker mice may also be significantly shorter and thinner at birth [34]. Degeneration involving disintegration of the cuticular plate, stereociliary disarray and fusion and hair cell expulsion was noted for the vestibular hair cells of jerker mice, but these changes happened later than in the cochlea, and hair cells in the cristae ampullares were largely spared [35].…”
Section: Jerker Deafness Mutation In the Mouse Espin Genementioning
confidence: 99%
See 1 more Smart Citation
“…Instead it may provide a balance between the conflicting needs for structural stability and the repair or renewal of structures at the stereociliary tip, not least those of the tip link anchorage. Eps8 could have a similar function in the longer stereocilia, possibly by acting as a "gated-capper" protein (15), in which it protects the actin barbed end from other capping proteins but allows those promoting elongation, such as espin (8,38).…”
Section: Loss Of Eps8l2 Is Associated With Severe Progressive Hearingmentioning
confidence: 99%
“…Different transcriptional start sites distinguish four major espin isoform size classes, which range from ~110 kDa tõ 25 kDa in apparent molecular mass and are designated 1-4, in order of decreasing size; splice variants are further specified alphabetically (Sekerková et al, 2004). Beyond bund ling actin filaments in a Ca 2+ -resistant fashion (Bartles et al, 1998;Chen et al, 1999), the espins appear to function in part to regulate the length of microvilli and stereocilia by increasing the steady-state length of the dynamic parallel-actin-bundle scaffold at their core Rzadzinska et al, 2005). Recently, we presented immunocytochemical evidence that espins are present at high levels in the microvilli of several other classes of sensory cell besides hair cells -including vomeronasal sensory neurons, Merkel cells, and solitary chemoreceptor cells -and suggested that espins might confer special properties on the microvillar specializations of sensory cells (Sekerková et al, 2004).…”
Section: Introductionmentioning
confidence: 99%